If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(n + 6) = -7(1 + -6n) Reorder the terms: 5(6 + n) = -7(1 + -6n) (6 * 5 + n * 5) = -7(1 + -6n) (30 + 5n) = -7(1 + -6n) 30 + 5n = (1 * -7 + -6n * -7) 30 + 5n = (-7 + 42n) Solving 30 + 5n = -7 + 42n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-42n' to each side of the equation. 30 + 5n + -42n = -7 + 42n + -42n Combine like terms: 5n + -42n = -37n 30 + -37n = -7 + 42n + -42n Combine like terms: 42n + -42n = 0 30 + -37n = -7 + 0 30 + -37n = -7 Add '-30' to each side of the equation. 30 + -30 + -37n = -7 + -30 Combine like terms: 30 + -30 = 0 0 + -37n = -7 + -30 -37n = -7 + -30 Combine like terms: -7 + -30 = -37 -37n = -37 Divide each side by '-37'. n = 1 Simplifying n = 1
| X^2+100x-1875=0 | | 12-4(-3x+5)-8x=20 | | 234/351 | | 7-5k=-43 | | 8x-2=5-x | | Sin(3x)cos(7x)-cos(3x)sin(7x)=-0.6 | | 4w-14=58 | | 6-7(7x+15)=244 | | 70+130+x+y=180 | | 4x+2x+7=6x-2x+2 | | 0.7(6x+5)=1.1-(x+3) | | -2(q-29)=q1/2(4)!-8q) | | 2x+22+4x+11=9x-15 | | Sin(3x)cos(7x)-cos(3x)sin(7x)=-0.06 | | 4(x-3)+2=14 | | -3(3x-8)+5(6-x)=-6 | | y-6/2=3-2y/5 | | -6x+9x=-4x+1 | | z=b-d/c | | -3/4d=6/8 | | 1x^2+1x-12=0 | | 4[r-8]=16-r | | -8/9f=32/9 | | 3/5f=12 | | F(6)=2x+4 | | z-(-3.5)=3.9 | | 7+3u=-5 | | 7/10w=35 | | 54=-8(n-6)+7(-6n+8) | | 0.5x+0.7=-1.8 | | 6x+4-8x=13-19x+17x-9 | | d=5abc |